Properties of bio-composite product from acacia strand and coconut veneer - Siti Noorbaini Sarmin (Songklanakarin Journal of Science and Technology (SJST), 2020)
Properties of bio-composite product from Acacia mangium strand and Cocos nucifera veneer were ascertained. Different strand sizes (10 mm, 15 mm and 20 mm) were used to create different combinations of layer arrangement; strandveneer-strand (SVS) and veneer-strand-veneer (VSV). Comply, a bio-composite product, was assessed for the mechanical and physical properties accordance with the European Standard. The value of MOR and MOE were found to be not significant when comparing SVS (10 mm and 15 mm) with 100% strand. Meanwhile, it was found that SVS (10 mm) with 100% strand had the highest value of internal bond and thickness swelling. Both layer arrangements were then being compared with plywood made by coconut veneer. Results showed that plywood had the highest value of MOR (51.54 MPa) and IB (0.66 MPa), VSV had the highest value of MOE (8037.79 MPa). For physical property the plywood had the best value of TS (12.19%).